2023
DOI: 10.1177/15910199231155288
|View full text |Cite
|
Sign up to set email alerts
|

Packing density and the angiographic results of coil embolization of intracranial aneurysms: A systematic review and meta-analysis

Abstract: Background Endovascular coil embolization (ECE) for intracranial aneurysms has been proven as an effective minimally invasive treatment. However, the aneurysm recanalization after coiling is a serious complication of this technique. Among all the proposed factors associated with recanalization, the impact of packing density (PD) is still controversial. Objective To clarify the role of PD in the aneurysm recanalization following ECE, via conducting a systematic review and meta-analysis. Methods A systematic lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…While there is a report of a close relationship between packing density and recanalization rate [28], other studies have reported that the presence or absence of complete embolization, rather than packing density per se, is a signi cant risk factor for recanalization and that packing density is not signi cantly correlated with recanalization [29,30]. In the present study, packing density was not included as a confounding factor because accurate volume embolization rates were not available for several cases.…”
Section: Discussionmentioning
confidence: 78%
“…While there is a report of a close relationship between packing density and recanalization rate [28], other studies have reported that the presence or absence of complete embolization, rather than packing density per se, is a signi cant risk factor for recanalization and that packing density is not signi cantly correlated with recanalization [29,30]. In the present study, packing density was not included as a confounding factor because accurate volume embolization rates were not available for several cases.…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies have suggested an association between packing density and recanalization [ 7 , 19 ]. However, more recent studies have presented conflicting results [ 8 , 10 ], leading to a controversial understanding of this relationship. Consistent with previous literature, a statistically significant correlation has been observed between smaller aneurysm size and higher packing density [ 19 ].…”
Section: Discussionmentioning
confidence: 99%